Therapeutic Drug Monitoring-Guided Linezolid Therapy for the Treatment of Multiple Staphylococcal Brain Abscesses in a 3-Month-Old Infant - Anna Cascone; Maia De Luca; Raffaele Simeoli; Bianca Maria Goffredo; Laura Cursi; Costanza Tripiciano; Lorenza Romani; Stefania Mercadante; Martina Di Giuseppe; Francesca Ippolita Calo Carducci; Davide Luglietto; Paola Bernaschi; et al. (Pathogens)
Brain abscesses are invasive infections of the central nervous system with a high level of treatment complexity especially in pediatric patients. Here, we describe a 3-month-old infant with multiple brain abscesses caused by methicillin-susceptible Staphylococcus aureus (MSSA). The patient was initially treated with empirical antibiotics (ceftriaxone, metronidazole, vancomycin). Upon MSSA identification, therapy was optimized by switching vancomycin to linezolid to improve tissue penetration. Therapeutic drug monitoring (TDM) was performed to check linezolid levels in the plasma and pus of the abscess, confirming drug penetration into brain tissue. A two-stage surgical drainage approach, consisting of repeated pus aspiration through an intracystic catheter, was then performed to achieve a significant reduction in abscess size. After nine weeks of antibiotic therapy, the patient was discharged in good clinical condition. This case highlights the role of linezolid for the treatment of complicated CNS infections and the importance of a multidisciplinary approach, combining TDM-based antibiotic therapy with timely and eventually repeated surgery, in order to effectively treat brain abscesses.